Indicateurs géochimiques et biologiques des changements environnementaux dans les lacs de l'Arctique canadien de l'Est - Narancic, Biljana (Université Laval, 2017)
The Arctic regions are warming at an alarming rate. However, the magnitude of climate change in the Canadian Arctic is not of the same intensity in all its sub-regions. While the West and North are warming rapidly, the eastern Canadian Arctic experienced climate stability until the turn of the last century. This thesis is a paleolimnological and hydrological case study of the eastern Canadian Arctic region, more specifically of southwestern Baffin Island and of the coastal regions of Hudson Bay in Nunavik (Northern Quebec, Canada). Studies of diatom assemblages from two cores and sedimentary characterization of four cores taken from Nettilling Lake (Baffin Island) allowed for the paleolimnological reconstruction of the region. Stable oxygen isotope signals preserved in diatom frustules allowed for the paleoclimatic and paleohydrological reconstruction of the region. High-resolution isotope analysis combined with the study of the specific composition of diatom assemblages were an important addition to paleoenvironmental reconstructions in the Lake Nettilling region showing that the postglacial history began with a marine transgression (ca. 8300 yrs cal. before present-BP), followed by a transitional brackish phase (ca. 7300 yrs cal. BP) leading to the freshwater lake environment (ca. 6000 yrs cal. BP) which persists to the present-day. The study of thermokarst lakes (permafrost thaw lakes) evaluated the influence of temperature, precipitation and permafrost degradation on the current water balance of 86 sites in Nunavik. A model of isotopic mass balance was used in the study area to establish the lake-specific input water sources and evaporation rates. The results suggest that these lakes are very sensitive to variations in precipitation and air temperature. Some lakes located in sporadic permafrost terrain are susceptible to evaporation as the near absence of permafrost thaw no longer provides a source of water that could compensate for the effect of evaporation in a landscape where permafrost is less degraded ...